Rare bird documentation form for Northern Goshawk at Hawkeye Wildlife Area, 1986 - Staudt, Thomas J.et al (1986)
Rare bird documentation form for a Northern Goshawk at Hawkeye Wildlife Area in Johnson County, IA on March 3, 1986. Epson - sheet feed